Novel oral anticoagulants and HIV: dabigatran use with antiretrovirals. (20th November 2015) - Perram, Jacinta; Joseph, Joanne; Holloway, Cameron
Abstract : Compatibility of novel oral anticoagulants in patients with HIV taking combined antiretroviral therapy has not been established, with no published reports of successful concurrent use. We present a case where chronic anticoagulation was indicated in a patient with treated HIV and non-valvular atrial fibrillation who refused warfarin therapy. The patient tolerated the combination, with dabigatran blood levels within the expected range at a standard dosing regimen, without evidence of bleeding or other adverse outcomes. While further research is needed to establish the role of novel oral anticoagulants in patients taking antiretrovirals, this case suggests that dabigatran may be a viable option for selected patients.